Distribution of inheritance mass-on the example of Anglo-Saxon law and “Indian law” systems - Bekzod Gadoev (Genius Journals, 2024)
This article analyzes the mass distribution of inheritance according to Anglo-Saxon law and “Indian law” in Uzbek legislation, characterized by laudatory characteristics of inheritance according to common parables. Schuningdeck, Anglo-Saxon inheritance law and ”Indian law " section, a section of inheritance rights relating, for example, to foreign States.
Keywords: Anglo-Saxon law family; Indian legal system; legal system of African countries